PENGARUH EKOSISTEM KEWIRAUSAHAAN, FAKTOR LINGKUNGAN DAN SOSIAL DENGAN FAKTOR DAYA SAING SEBAGAI MODERASI TERHADAP PERTUMBUHAN EKONOMI DI NEGARA BERKEMBANG - Susanti, Susanti; Sofia Keumalasari; Nurfiani Syamsuddin; Ika Rezvani Aprita (Nusantara Hasana Journal, 2025)
This study analyzes the influence of the entrepreneurial ecosystem, environmental and social factors on economic growth with competitiveness as a moderating variable. Using panel data from 29 developing countries during the period 2016–2019, this study developed four panel data regression models and tested the hypotheses with statistical tests. Empirical results show that the influence of the entrepreneurial ecosystem on economic growth is more significant in developed countries than in developing countries. Conversely, the influence of the entrepreneurial ecosystem on competitiveness is higher in developing countries. However, when competitiveness acts as a moderating variable, its contribution to economic growth is greater in developed countries, especially in its role as a moderator. These findings indicate the importance of policies that support entrepreneurship in developing countries, as well as the need for cross-sector collaboration to create an ecosystem that can encourage the emergence of innovative entrepreneurs for inclusive and sustainable economic growth.